2007
DOI: 10.4049/jimmunol.178.1.389
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Reactivity and 1.4-Å Crystal Structure ofMalassezia sympodialisThioredoxin (Mala s 13), a Member of a New Pan-Allergen Family

Abstract: We have identified thioredoxins (Trx) of Malassezia sympodialis, a yeast involved in the pathogenesis of atopic eczema, and of Aspergillus fumigatus, a fungus involved in pulmonary complications, as novel IgE-binding proteins. We show that these Trx, including the human enzyme, represent cross-reactive structures recognized by serum IgE from individuals sensitized to M. sympodialis Trx. Moreover, all three proteins were able to elicit immediate-type allergic skin reactions in sensitized individuals, indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
76
1
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(80 citation statements)
references
References 44 publications
(51 reference statements)
0
76
1
1
Order By: Relevance
“…Therefore it can be concluded that the Asp f 9 cDNA sequence is correct, and that the published Asp f 16 peptide sequence results from frameshift, other sequencing errors, or derives from a different A. fumigatus strain; (iii) Asp f 17, originally described as a cDNA encoding a 191 amino acid protein [24], is incomplete and the complete gene encodes a protein of 284 amino acids; and (iv) the postulated sequence of the Asp f 56 kDa allergen not included in the official allergen database, which was derived from a short peptide obtained from a biochemically purified protein [28] is not predicted to be encoded in any of the sequenced Aspergillus genomes. All other A. fumigatus allergens reported in the official allergen database as well as the sequences of the recently cloned thioredoxins (Asp f 28, Asp f 29) [29], cyclophilins (Asp f 11, Asp f 27) [30], and Phi A cell wall protein (Asp f 34, Glaser unpublished) sequences showed virtually a 100% identity with the genome sequence, confirming at genomic level the validity of cDNA cloning approaches for the elucidation of allergen repertoires. The whole repertoire of A. fumigatus allergens included in the official allergen list reported in Table 2 have been produced as highly pure recombinant allergens and evaluated for their IgE-binding capacity in vitro.…”
Section: The Allergen Repertoire Of Aspergillus Fumigatusmentioning
confidence: 83%
See 4 more Smart Citations
“…Therefore it can be concluded that the Asp f 9 cDNA sequence is correct, and that the published Asp f 16 peptide sequence results from frameshift, other sequencing errors, or derives from a different A. fumigatus strain; (iii) Asp f 17, originally described as a cDNA encoding a 191 amino acid protein [24], is incomplete and the complete gene encodes a protein of 284 amino acids; and (iv) the postulated sequence of the Asp f 56 kDa allergen not included in the official allergen database, which was derived from a short peptide obtained from a biochemically purified protein [28] is not predicted to be encoded in any of the sequenced Aspergillus genomes. All other A. fumigatus allergens reported in the official allergen database as well as the sequences of the recently cloned thioredoxins (Asp f 28, Asp f 29) [29], cyclophilins (Asp f 11, Asp f 27) [30], and Phi A cell wall protein (Asp f 34, Glaser unpublished) sequences showed virtually a 100% identity with the genome sequence, confirming at genomic level the validity of cDNA cloning approaches for the elucidation of allergen repertoires. The whole repertoire of A. fumigatus allergens included in the official allergen list reported in Table 2 have been produced as highly pure recombinant allergens and evaluated for their IgE-binding capacity in vitro.…”
Section: The Allergen Repertoire Of Aspergillus Fumigatusmentioning
confidence: 83%
“…However, only three crystal structures derived from fungal allergens, ribotoxin (Asp f 1) [45, 46], MnSOD (Asp f 6) [65] from A. fumigatus and a Xylanase from Paecilomyces variotii [66] have been reported so far. Recently the crystal structures of a cyclophilin of A. fumigatus (Asp f 11) [61] and Malassezia sympodialis (M. sympodialis) (Mala s 6) [30], as well as the crystal structure of thioredoxin of M. sympodialis (Mala s 13) [29], and Mala s 1, a major allergen of M. sympodialis with unknown function [67] have been determined at high resolution.…”
Section: Structural Aspects Of Fungal Allergensmentioning
confidence: 99%
See 3 more Smart Citations